Finding our way through the traffick : navigating the complexities of a Christian response to sexual exploitation and trafficking - Crawford, Christa Foster; Miles, Glenn; Velazco, G. A. (Gundelina A.) (Regnum studies in mission., 2017)
"Where Do We Go from Here? We want to help others find freedom - lasting freedom - from trafficking and exploitation. But the process is as fraught with challenges as it is filled with calls to do better. What are the best routes to effectiveness? How do we avoid common pitfalls? This book brings together decades of experience to help us navigate the complexities of responding to holistic needs in prevention, intervention, rehabilitation, and reintegration. It also explores how to prepare ourselves as organizations and individuals for the journey ahead. This companion to Stopping the Traffick is an essential guide for practitioners, donors, and academics to successfully Find Our Way through the Traffick."--Publisher.